Menanamkan Kesadaran Bela Negara pada Anak Usia Sekolah - Iman Permana; Liswandi Liswandi; Aulia Azzahra; Bunga A.B Tampubolon; Evita Liana; Kentaro Victor Oeripan; Lila Nur Haliza; Lyanni Felichia; Nyayu Tiara Berlian Anjeli; Pooja Maulaya Putri; Ribka Hidayati Munthe; Sabillia Orchida Apriliani; Salwa Salsabila Basyasyah; Sarah Dameria Sembiring; Tabitha Vivi Wijayanti; Yanuardi Wibisono (ACADEMICS IN ACTION Journal of Community Empowerment, 2021)
Defending the State of Indonesia is the attitude and behavior of Indonesian citizens who are imbued with their love for the Unitary State of the Republic of Indonesia (NKRI) based on Pancasila and the 1945 Constitution. Socialization of defending the State is an effort to embed the values of defending the State towards the individuals of the Indonesian society. This socialization activity to embed the awareness of defending the State is directly aimed to the school-aged children to embed the importance of defending the State since early age. The socialization that has been carried out through online and offline methods is expected to be one of the key steps aimed at making the next generations love their own nation since early age, so they become individuals who love NKRI when they grow up in the future.